Pulmonary delivery of siRNA-loaded lipid-polymer hybrid nanoparticles: Effect of nanoparticle size - Abishek Wadhwa; Thomas R. Bobak; Lennart Bohrmann; Reka Geczy; Sathiya Sekar; Gowtham Sathyanarayanan; Jörg P. Kutter; Henrik Franzyk; Camilla Foged; Katayoun Saatchi; Urs O. Häfeli (Elsevier, 2023)
Nanomedicines based on nanoparticles rely both on the potency of the drug as well as the efficiency of the delivery system, for which particle size plays a crucial role. For the intracellular delivery of small interference RNA (siRNA), lipid-polymer nanoparticle (LPN) hybrid systems constitute a safe and highly effective class of delivery systems. In the present study, we employ a microfluidics method for the manufacturing of spherical siRNA-loaded LPNs for pulmonary delivery with distinct size distributions with average diameters of approximately 70, 110, and 220 nm. We designed an optically clear, inexpensive thiol-ene polymeric microfluidic chip prototype that is compatible with standard 'soft-lithography' techniques, allows for replica molding, and is resistant to harsh solvents. By using SPECT/CT in vivo imaging, we show comparable pulmonary clearance patterns of all three differently sized LPN formulations following intratracheal administration. Also, negligible accumulation in the liver was observed.